Comparison of the Efficacy of Everolimus-Eluting Stents and Paclitaxel-Eluting Balloon Angioplasty for Coronary In-Stent Restenosis: A Systematic Review and Meta-Analysis - Zhili Wei; Ziran Luo; Yixvan Chang; Zhijing An; Sai Jin; Jianke Rong; Bing Song (Reviews in Cardiovascular Medicine)
Background: The aim of the study was to systematically evaluate and compare the efficacy of everolimus-eluting stents (EESs) and paclitaxel-coated balloons (PCBs) in treating patients with in-stent restenosis (ISR). Methods: We performed a comprehensive search of the PubMed, Cochrane Library, Web of Science, and Embase databases up to August 2024. Two researchers independently conducted literature retrieval, screening, data inclusion, and quality assessment. A collaborative meta-analysis was performed using Stata 17.0. Results: A total of ten randomized controlled trials (RCTs) were included, all assessed using the Cochrane quality assessment tool and were categorized as having a low risk of bias. The analysis revealed a significantly higher need for target lesion revascularization in the PCB group compared to the EES group (odds ratio (OR) = 2.74, 95% confidence interval (CI) (1.80–4.16), p < 0.001, I2 = 38.6%). There were no significant differences between the EES or PCB treated ISR patients in terms of all-cause mortality, cardiac death, myocardial infarction, target lesion revascularization, and stent thrombosis within one year. Subgroup analyses based on ISR causative factors showed consistent results with overall findings and significantly reduced heterogeneity. Conclusion: PCBs are associated with a higher frequency of target lesion revascularization compared to EES in the treatment of ISR. However, there are no significant differences in other outcome indicators. Therefore, EES is recommended as the preferred treatment for ISR in clinical decision-making. The INPLASY registration: INPLASY202480079, https://inplasy.com/inplasy-2024-8-0079/.